Sustainability Concerns and Investor Responses to Earnings Announcements - Akhmad Riduwan; Andajani Andajani (Universitas Pasundan, 2019)
This study aims to examine the effects of corporate sustainability concerns on investor responses to earnings announcements (earnings response coefficient). The study was conducted on 110 companies that announced sustainability disclosures based on Global Reporting Initiative standards during the 2008–2017 observation period. With multiple linear regression models, the results of the study show that companies' concerns regarding economic, environmental, and social sustainability have a positive effect on investor response to earnings announcements. The results of this study imply that investors have the awareness and confidence that financial performance manifesting as an investment return is not an instant goal, but must be sustainable over the long–term. Investors are aware that investment returns, directly or indirectly, are influenced by social stability and environmental sustainability.